Implementation of Hidden Curriculum in Social Science Subjects in Pesantren: Encouraging Student Engagement in the 21st Century - Fismanelly, Fismanelly; Montessori, Maria; Indrawadi, Junaidi; Fatmariza, Fatmariza; Jannah, Miftahul (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to describe the comparison between traditional teaching methods and the hidden curriculum approach in learning social science subjects at Pondok Pesantren Ashhabul Yamin Lasi. This research aims to understand how the hidden curriculum affects student engagement in social science learning at the boarding school. The research method used is a qualitative study with participant observation techniques and in-depth interviews with teachers and students. The result of the hidden curriculum on student engagement can be extended by looking at various aspects of its influence in the 21st century. This approach encourages the development of metacognitive skills, enhances creativity and innovation, and deepens students' understanding through experiential learning. The teacher-student relationship is also strengthened, while students are prepared for lifelong learning by promoting independent learning skills. Thus, the hidden curriculum is not only about knowledge, but also shaping individuals who are ready to face the challenges of the 21st century.